Lipids and leptin level in natives of Kyrgyzstan - Erkin Mirrakhimov; Alina Kerimkulova; Olga Lunegova; Aibek Mirrakhimov; Nazira Alibaeva; Malik Nabiev (KARE Publishing, 2014)
Objectives: A possible link between obesity and impaired lipid metabolism is leptin, the 167-amino acid protein, secreted by adipocytes. The content of leptin in the body is closely associated with body mass index (BMI). Data obtained from studies on the association of leptin with dyslipidemia are contradictory. The level of leptin has not been studied in the ethnic Kyrgyz population previously. The purpose of this study was to investigate the relationship between leptin and lipid parameters in a group of ethnic Kyrgyz. Study design: The study included 322 ethnic Kyrgyz (145 males, 177 females) aged ≥30 years, living in Kyrgyzstan. Measurement of anthropometric parameters (height, weight, waist circumference [WC], hip circumference [HC]) and blood pressure (BP) was done. Laboratory tests included blood glucose (fasting) in plasma, lipid profile (total cholesterol [TC], triglycerides [TG], high-density lipoprotein [HDL] cholesterol, low-density lipoprotein [LDL] cholesterol), and serum leptin. Results: Leptin was positively correlated with BMI, WC and TG in both sexes and with TC in males. Conclusion: Leptin is associated with BMI, WC and TG in both sexes of Kyrgyz and with TC in Kyrgyz males.